Characterization of a Cavanillesia platanifolia young plantation in the Colombian Banana Zone - Castañeda-Garzón, Sandra Liliana; Arenas-Rubio, Isueh; Argüelles-Cárdenas, Jorge Humberto; Montero-Cantillo, Yesith Darith; Gutiérrez-Berdugo, Iván Antonio; Zuluaga-Peláez, Jhon Jairo (Instituto de Ecología, A.C., 2023)
The macondo tree [Cavanillesia platanifolia (Bonpl.) Kunth] is a native species, characteristic of dry forest, beautiful landscape, and cultural value; however, phenotypic variability and canopy opacity are unknow. The Corporación Colombiana de Investigación Agropecuaria – AGROSAVIA has a young plantation of this species in the Zona Bananera, department of Magdalena, in which growth and adaptation to agroecological conditions are evaluated. The characterization included 30 plant morphological descriptors to evaluate 83 trees of 5.3 years of age as well as the evaluation of canopy structure in three plots. The qualitative and quantitative descriptors were analyzed by multiple correspondence analysis and principal components analysis respectively to reduce data dimensionality, followed by cluster analysis using WARD algorithm for grouping individuals. 19 quantitative and qualitative tree and leaf variables showed variation between the individuals of C. platanifolia, which were classified into five groups accumulating 99.87% of the original variability. Individuals with potential of use in agroforestry systems, arboriculture and biomass production were identified in this clusters. The juvenile individuals of C. platanifolia have a low leaf area index (0.29 to 2.03) and canopy openness among 17% and 71%.